The Behavioral Theory of the Firm: Foundations, Tenets and Relevance - Isabirye, Joel (Technium Social Sciences Journal, 2021)
The Behavioral Theory of the Firm has for over fifty years shaped a section of economic thought on the nature and functioning of the firm. In this paper, this theory is reviewed with a focus on its foundations, tenets and relevance. The paper posits that the Behavioral Theory of the Firm set out to distinguish from previously known analytical models of the firm. It drew in an interdisciplinary model and explored the firm in more diverse ways than before. The foundations of the theory, its tenets and relevance are discussed. Often traced to Richard Cyert and James March, whose A Behavioral Theory of the Firm (1963) text seemed to commence this theory, the evidence shows that their seminal work was one of several other contributions to its development. What is not in dispute is that the seeds for a Behavioral Theory of the Firm were sown at the Carnegie Mellon University in or around the mid-20th century. Broadly the Behavioral Theory of the Firm conceives the firm as a unit of production with goals, and a dominant coalition that harmonizes different interests of its stakeholders into those goals.